Task Related Training Approach dalam Mengeliminasi Kecemasan dan Keseimbangan serta Meningkatkan Kemandirian Beraktifitas pada Pasien Pasca Stroke - Khomarun; Wawan Ridwan Mutaqin (Journal of Health and Therapy, 2022)
Stroke survivors often experience disabilities that hinder their daily activities and make them dependent on others. The problem is that the post-stroke side effects are balance disorders, anxiety, and independence. This research is an experimental study with the one group pretest-posttest design with control. The sample of this research is 50 respondents. Data were analyzed using t test. The results of the analysis showed that there was a significant difference in the level of anxiety and the level of independence before and after the Task Related Training treatment because the significance value was less than 5% (0.000 <0.05). On the other hand, the results of the balance level test did not show any difference between before and after the Task Related Training treatment, because the significance value was more than 5% (0.474>0.005). The conclusion of this study was found the effect of Task Related Training on anxiety, independence of post-stroke patients, but no effect was found on the balance of post-stroke patients.